Testing for multidimensional inequality in Malaysia - Mohamed, Zunika; Said, Rusmawati (2013)
This paper investigates the inequality phenomenon in Malaysia under a multidimensional framework. To do so, we construct a multidimensional index of inequality based on a currently introduced method of Lugo and Decancq (2009). Our index is based on four dimensions: finance, education, standard of living and housing. Our result uncovers that while the quantum of multidimensional inequality is lower than the standard income measure, disparities on the basis of region, gender and ethnicity also form an integral part of inequality under the multidimensional framework in Malaysia.